Chemistry of hornblendes from the Deosai volcanics, Baltistan, northern Pakistan - Hamidullah, Syed (Journal of Himalayan Earth Sciences, 1994)
Seventy-eight core to margin spot analyses of 8 hornblende phenocrysts from an andesitic basalt of Deosai Plateau, Baltistan, N. Pakistan, are presented in the form of means and standard deviations. The data show an igneous parentage for these hornblendes. Chemical variations do not agree with commonly accepted substitutions for igneous homblendes and an overall core to margin substitution of [xFe3++xivAl+xTi+xMg+xNaB = xviAl+xFe2+(±xMn)+xCa+xSi+xA-site] type is suggested with the former set of cations higher in cores and the latter in margins. A tentative temperature range of 875-700oC and a PH2O range of 6-4.2kb are suggested for the crystallization of these hornblendes. It is also suggested that like clinopyroxene the Deosai hornblendes carry unusual chemical features which may be related to variations in physio-chemical environment of the magmatic chamber, and for that reason, possibly, of the source region.